Lower Circulating Cell-Free Mitochondrial DNA Is Associated with Heart Failure in Type 2 Diabetes Mellitus Patients - Berezina, T. A.; Kopytsya, M. P.; Petyunina, O. V.; Berezin, A. A.; Obradovic, Z.; Schmidbauer, L.; Lichtenauer, M.; Berezin, A. E.; Березін, Олександр Євгенійович (My University, 2023)
Cell-free nuclear (cf-nDNA) and mitochondrial (cf-mDNA) DNA are released from damaged cells in type 2 diabetes mellitus (T2DM) patients, contributing to adverse cardiac remodeling, vascular dysfunction, and inflammation. The purpose of this study was to correlate the presence and type of cf-DNAs with HF in T2DM patients. A total of 612 T2DM patients were prescreened by using a local database, and 240 patients (120 non-HF and 120 HF individuals) were ultimately selected. The collection of medical information, including both echocardiography and Doppler imagery, as well as the assessment of biochemistry parameters and the circulating biomarkers, were performed at baseline. The N-terminal brain natriuretic pro-peptide (NT-proBNP) and cf-nDNA/cfmtDNA levels were measured via an ELISA kit and real-time quantitative PCR tests, respectively. We found that HF patients possessed significantly higher levels of cf-nDNA (9.9 2.5 mol/L vs. 5.4 2.7 mol/L; p = 0.04) and lower cf-mtDNA (15.7 3.3 mol/L vs. 30.4 4.8 mol/L; p = 0.001) than those without HF. The multivariate log regression showed that the discriminative potency of cf-nDNA >7.6 mol/L (OR = 1.07; 95% CI = 1.03–1.12; p = 0.01) was higher that the NT-proBNP (odds ratio [OR] = 1.10; 95% confidence interval [CI] = 1.04–1.19; p = 0.001) for HF. In conclusion, we independently established that elevated levels of cf-nDNA, originating from NT-proBNP, were associated with HF in T2DM patients.
Keywords: type 2 diabetes mellitus; heart failure; cell-free DNA; liquid biopsy; biomarkers